Ultra-sensitive gas phase detection of 2, 4, 6-trinitrotoluene by non-covalently functionalized graphene field effect transistors. Issue 3 (10th December 2019) - Gajarushi, Ashwini S.; Surya, Sandeep G.; Walawalkar, Mrinalini G.; Ravikanth, M.; Rao, V. Ramgopal; Subramaniam, Chandramouli
Abstract : Dirac point of non-covalently functionalized graphene field effect transistors has been demonstrated as a reliable parameter for rapid (∼40 s), reliable and ultra-sensitive (ppm-level) detection of 2, 4, 6-trinitrotoluene under ambient conditions. Abstract : The high energy density (4.2 MJ kg −1 ) and low vapour pressure (7.2 × 10 −9 atm) of chemical explosives such as TNT (2, 4, 6-trinitrotoluene) pose a grave security risk demanding immediate attention. Detection of such hazardous and highly challenging chemicals demands specific, ultra-sensitive and rapid detection platforms that can concomitantly transduce the signal as an electrical readout. Although chemo-sensitive strategies have been investigated, the majority of them are restricted to detecting TNT from solutions and are therefore not implementable in real-time, on-field situations. Addressing this demand, we report an ultra-sensitive (parts-per-billion) and rapid (∼40 s) detection platform for TNT based on non-covalently functionalized graphene field effect transistors (GFETs). This multi-parametric GFET detector exhibits a reliable and specific modulation in its Dirac point upon exposure to TNT in the vapour phase. The chemical specificity provided by 5-(4-hydroxyphenyl)-10, 15, 20-tri( p -tolyl) zinc porphyrin (ZnTTPOH) is synergistically combined with the high surface sensitivity of graphene through a non-covalent functionalization approach to realise p-doped GFETs (Zn-GFETs). Such a FET platform exhibits extremely sensitive shifts in Dirac point (Δ D P ) that correlate with the number of nitro groups present in the analyte. Analytes with mono-, di-, and tri-nitro substituted aromatic molecules exhibit distinctly different Δ D P, leading to unprecedented specificity towards TNT. Additionally, the Dirac point of Zn-GFETs is invariant for common and potential interferons such as acetone and 2-propanol (perfume emulsifiers) thereby validating their practical applicability. Furthermore, the Δ D P is also manifested as changes in the contact potential of GFETs, indicating that sub-monolayer coverage of ZnTTPOH is sufficient to modulate the transfer characteristics of GFETs over an area 1000 times larger than the dopant dimensions. Specifically, ZnTTPOH-functionalized GFETs exhibit p-doped behaviour with positive Δ D P with respect to pristine GFETs. Such p-doped Zn-GFETs undergo selective charge-transfer mediated interactions with TNT resulting in enhanced electron withdrawal from Zn-GFETs. Thus the Δ D P shifts to a higher positive gate voltage leading to the dichotomous combination of the highest signal generation (1.2 × 10 12 V mol −1 ) with ppb level molecular sensitivity. Significantly, the signal generated due to TNT is 10 5 times higher in magnitude compared to other potential interferons. The signal reliability is established in cross-sensitivity measurements carried out with a TNT–mDNB (1 : 10 molar ratio) mixture pointing to high specificity for immediate applications under atmospherically relevant conditions pertaining to homeland security and global safety.